The Influence Of ISO Certificate On Quality Evaluation Of Students: A Case Study At Ishik University - Demir, Ahmet; Guven, Sinan (Advances in Social Sciences Research Journal, 2017)
In this study, the influence of ISO certificate on student satisfaction has been analyzed through investigating ISO standards which are implemented at Ishik University. Therefore, the impact of ISO certificate on education quality and its effects on student satisfaction have been studied. The data used in this study consists of information gathered through questionnaires and university database. The questionnaires were distributed to randomly chosen fifty students from each department. In this study three different scales were used: A questionnaire that includes 14 questions to assess courses and lecturers and a questionnaire that includes 10 questions to assess department heads. The collected data has been analyzed through Statistical Package for Social Sciences (SPSS). The influence of ISO certificate on student satisfaction is the major theme in the study. As a result, it has been found that when ISO implementation at Ishik University worked, the results have been shown on the findings and conclusion parts.